The Yoga Kitchen : OVER 100 VEGETARIAN RECIPES TO ENERGISE THE BODY, BALANCE THE MIND & MAKE FOR A HAPPIER YOU - Parsons, Kimberley; Cohen, Lisa (London : Quadrille, 2016)
The Yoga Kitchen teaches you that by eating holistic recipes you can nourish your mind, strengthen your body and bring more balance into your life. All the recipes are vegetarian and gluten-free, allowing you to improve your health, build your inner-core, increase your energy and support your spiritual development. Kimberly Parsons is the owner of The Retreat Cafes, that have become an integral part of London's yoga scene, and in her first book she brings her healthful recipes and yogic principles straight into your kitchen. The recipes in The Yoga Kitchen are divided into chakra-based chapters; Ground, Flow, Soul, Nurture, Strengthen, Vitalise and Core. From Green quinoa burgers and Sweet potato gnocchi with walnut pesto to Tahini & pistachio cookies and Goji tart with Passionfruit curd it has never been easier to eat in a balanced way with these delicious and inspiring yoga-based recipes
t Naturopathy -- t Flow -- t Strengthen -- t Holistic dispensary.
Includes index
Keywords: Yoga cooking; Vegetarian cooking; Cookbooks